2020
DOI: 10.1111/jbi.13829
|View full text |Cite
|
Sign up to set email alerts
|

Global biogeographical patterns in the diet of a cosmopolitan avian predator

Abstract: We are grateful to Roberto Ambrosini and Alexandre H. Hirzel for their invaluable help in statistical analyses and map production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 76 publications
3
53
0
Order By: Relevance
“…According to many studies, this owl species is a typical small mammal specialist (Marti 1988, Bonvicino & Bezerra 2003, Charter et al 2009, which was also confirmed by a recent biogeographical assessment of the cosmopolitan Common Barn-owl group's (Tyto alba species complex) trophic ecology at global scale (Romano et al 2020). However, Barn Owls frequently select a given prey species and/or group, and based on their functional response, switch easily between prey items in their foraging strategy (Yom-Tov & Wool 1997, Tores et al 2005, Romano et al 2020. According to the 'alternative prey hypothesis', if the main prey species declines in the given year, generalist predators can show dietary shifts and switch to alternative prey (Angelstam et al 1984), which was detected in case of raptors (Reif et al 2001, Riegert et al 2009, Kreiderits et al 2016, Dementavičius et al 2020 and different owls (Korpimäki et al 1990, Jędrzejewski et al 1994, Sasvári et al 2000, Riegert et al 2009, including also the Common Barn-owl (Roulin 2004a, Tores et al 2005, Charter et al 2015, Baudrot et al 2016.…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…According to many studies, this owl species is a typical small mammal specialist (Marti 1988, Bonvicino & Bezerra 2003, Charter et al 2009, which was also confirmed by a recent biogeographical assessment of the cosmopolitan Common Barn-owl group's (Tyto alba species complex) trophic ecology at global scale (Romano et al 2020). However, Barn Owls frequently select a given prey species and/or group, and based on their functional response, switch easily between prey items in their foraging strategy (Yom-Tov & Wool 1997, Tores et al 2005, Romano et al 2020. According to the 'alternative prey hypothesis', if the main prey species declines in the given year, generalist predators can show dietary shifts and switch to alternative prey (Angelstam et al 1984), which was detected in case of raptors (Reif et al 2001, Riegert et al 2009, Kreiderits et al 2016, Dementavičius et al 2020 and different owls (Korpimäki et al 1990, Jędrzejewski et al 1994, Sasvári et al 2000, Riegert et al 2009, including also the Common Barn-owl (Roulin 2004a, Tores et al 2005, Charter et al 2015, Baudrot et al 2016.…”
Section: Introductionsupporting
confidence: 57%
“…Kulcsszavak: reprodukciós kimenet, táplálékfogyasztás, alternatív zsákmány, gradáció 1 University of Pécs, Faculty of Sciences, Institute of Biology, Department of Ecology, 7624 Pécs, Ifjúság utca 6., Hungary 2 Baranya County Group of BirdLife Hungary, 7632 Pécs, Siklósi út 94., Hungary BirdLife Hungary, 1121 Budapest, Költő utca 21., Hungary * corresponding author, e-mail: hgypte@gamma.ttk.pte.hu prey were reported by studies particularly in arid environments, where food intake results supported that the Common Barn-owl is a rather selective opportunistic predator (Heywood & Pavey 2002, Tores et al 2005, McDowell & Medlin 2009, Romano et al 2020.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…T. alba and T. javanica). The Tyto genus is composed of predator species only, hunting mainly small mammals but potentially shifting on other food sources when the prevalent prey is scarce (Taylor, 2003;Romano et al, 2020b). A possible interpretation for this result is that opportunistic predators might be less affected by the selective pressures imposed by peaks of food abundance than, for example, herbivore and insectivore species.…”
Section: Discussionmentioning
confidence: 99%
“…Prey selection on islands is limited by the presence of potential prey species and varies between individual islands. Although numerous factors can influence prey selection in owls (Comay & Dayan, 2018;Romano et al, 2020), we hypothesize that on islands the island's size, distance from the mainland and, as a proxy for urbanization, human population density also affect the pattern of the barn owl's prey composition. In this study, we present primary data on the diet of the barn owl on the Adriatic island of Korčula (Croatia) and include these results in a meta-analysis of available data on the barn owl diet across Mediterranean islands.…”
Section: Introductionmentioning
confidence: 99%